NATIONAL ROADS MANAGEMENT USING MARKOV CHAIN MODEL (CASE STUDY: NATIONAL ROADS IN BANTEN PROVINCE ) - NUGROHO, ANTON
Pavement performance modeling is required in road maintenance planning to determine the type of treatment to be performed in the future. The difficulty often faced by road managers is that it is not easy to predict pavement conditions and budgets that may not be available at the end of each planning year. This study discuss the approach of Markov Chain model to predict pavement conditions by using IRI (International Roughness Index) value. To illustrate budgets limitation, budget allocation scenario applied to see the impact on road performance during the year of analysis. Determination of road maintenance priority due to limitation of budget allocation is done by Analytical Hierarchy Process (AHP) method. The Markov Chain model modeled the initial condition of the pavement as the initial distribution of pavement conditions and the probability of future road condition changes obtained from the data of road condition changes in previous years as the Transitional Probability Matrix (TPM). 4 types of maintenance (Routine, Periodical, Rehabilitation, and Reconstruction) that can be selected for road maintenance is based on the percentage of road damage conditions. AHP is used to determine the order of importance of the annual road maintenance program plan over the next 10 years with various budgeting scenarios. 3 maintenance budget scenario were used in this study. This study provides results: 1. The markov chain model for road maintenance management shows a fairly good maintenance pattern, where road maintenance in the form of repairing action is done in the 2-3 year range. 2. The use of AHP is particularly suited in determines priority of road segments in the annual program planning for 10 years. 3. From the budgeting scenario, it is found that the smaller the budget provided for road maintenance will result in increased amount of funds needed to maintain road life cycle than when provided funds in accordance with their needs.